Uji Mutu Fisik dan Analisis Nilai Sun Protection Factor (SPF) Krim Tabir Surya Ekstrak Daun Kelor (Moringa oleifera L.) - Damayanti, Windy Aulia; Cahyani, Erlien Dwi; Nurcahyani, Diah (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2024)
Solar radiation can cause negative effects on human skin such as skin pigmentation, skin cancer, sunburn and aging, so protection is needed, one of which is sunscreen use. Moringa leaves (Moringa oleifera L.) contain flavonoid, secondary metabolite which is effective as photoprotectors because of their ability to absorb UV light and can be formulated into cream preparations. The aim of this research was to evaluate the physical quality and SPF value of 3 Moringa leaf extract cream formulas. The results of the physical quality evaluation for homogeneity, pH and organoleptics have met the requirements. Spreadibility test shows that formula I has a spreading power per load of between 5-6.23cm. The viscosity test showed that all formulas had good average viscosity results, namely formula I 23111 cPs, formula II 22670 cPs, and formula III 20170 cPs. The largest SPF test result was formula III which contained 5% extract which had a value of 4.8653 with medium SPF potential.